Forest deforestation in the Brazilian Amazon states and its impacts on natural resources: construction of statistical-econometric panel model for 2000-2018 - CARVALHO, André Cutrim (Universidade Federal de Campina Grande, 2021)
In Brazil, deforestation in the Amazon is the main factor which is responsible for the destruction of natural resources and environment degradation. Economic growth and improving income distribution, for example, contribute to an increased demand for land and to the expansion of livestock production. Thus, in order to analyze the effects of economic growth and income distribution on natural resources, first it is necessary to distinguish the dynamics of the economic growth (whether slow or accelerated); and second, it is essential to know the form in which economic growth is taking place: whether through the extensive absorption of using factors of production; or whether through intense absorption with an increase in the productivity of the factors of production due to technical innovations; and third, the fact that the economy grows in a finite ecosystem implies an increase in opportunity costs. The effect of deforestation ultimately affects economic productivity and also provokes other ecological and socioeconomic disruptions. The aim of this paper is to analyze the impact of deforestation on the natural resources of the area known as Legal Amazon, during the period 2000-2018. For this, statistical-econometric instruments from panel modeling have been used. The central conclusion is that the main regressors associated with the rate of deforestation in the surveyed states continue to be the significant causes of this problem throughout the region. Thus, it is assumed that deforestation in the Amazon is, in fact, the main factor responsible for the destruction of natural resources. However, it cannot be denied that extensive livestock production continues to be the main activity responsible for the significant increase in deforestation in the region.